The cephalic morphology of the Gondwanan key taxon Hackeriella (Coleorrhyncha, Hemiptera) - Spangenberg, Rico (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2013)
External and internal head structures of Coleorrhyncha, a key-taxon within the Hemiptera, are described in detail and documented using modern techniques. The main focus is on Hackeriella veitchi, but two additional representatives of the Gondwanan relict group were also examined, and also head structures of Enicocephalidae, a member of a potentially basal heteropteran lineage. Features were compared to those documented in literature for the Sternorrhyncha, Auchenorrhyncha, and Heteroptera. Coleorrhyncha are characterized by highly modified head structures and correspondingly an entire series of autapomorphies, such as for instance a strongly flattened head capsule with fenestrations. However, they also display features that are likely plesiomorphic compared to members of other hemipteran groups. These include the almost complete tentorium and the lack of the gula. The sistergroup relationship between Coleorrhyncha and Heteroptera is well supported by cephalic features. Potential synapomorphies are the presence of a distinct mandibular sulcus, the reduced number of antennomeres, the absence of clasping organs in the labial groove, coiled accessory salivary ducts, the presence of a small cervical muscle M1a (M. pronotopostoccipitalis medialis), the presence of a second mandibular promotor M14 (M. zygomaticus mandibulae), the presence of M28 (M. verticopharyngalis), and M30 (M. frontobuccalis posterior).